All stirred up : suffrage cookbooks, food, and the battle for women's right to vote - Kumin, Laura (Food writer) (Pegasus Books, 2020)
A look at how suffragettes brought their political messages into American homes through cookbooks that appealed to women in nonthreatening and accessible ways and ran counter to the militant and stern caricatures often associated with the movement.